Метод конформационного поиска для длинных полипептидных цепей, основанный на анализе энергетической функции - Щечкин, И.В.; Гуща, Т.О. (Видавничий дім "Академперіодика" НАН України, 2007)
The algorithm is proposed to search a conformational space of long flexible polypeptide chains. It consists in performing a series of geometry optimization runs by a gradient-based method using the atom-atom pairwise potential sum as a target function. Only a portion of pairwise terms is taken into account in each run. The algorithm was employed for the conformational analysis of the loop-like 125–167 fragment of human serum albumin treating the rest of the molecule as a rigid structure. Several stable conformers of the fragment were obtained that considerably differ by their 3D-structure from the original one. Some of the newly found conformers have no major attractive nonbonded contacts with the protein globule, and some of them form hydrogen bonds with other domains of the molecule. The latter enables us to suppose that the conformational transition of the 125–167 fragment can affect the mutual mobility of domains.